Electrochemistry of tris(2, 2′-bipyridyl) cobalt(II) in ionic liquids and aprotic molecular solvents on glassy carbon and platinum electrodes. (20th October 2015) - Cabral, Diogo; Howlett, Patrick C; Pringle, Jennifer M.; Zhang, Xinyi; MacFarlane, Douglas
Graphical abstract: Highlights: The [Co(bpy)3 ] 2+/3+ redox reaction is chemically reversible. The [Co(bpy)3 ] 1+/2+ redox reaction is chemically reversible under certain conditions. Better electrochemical reversibility is observed on glassy carbon rather than platinum. The rate constants are similar in the ionic liquids and in the aprotic molecular solvents. At 40 °C, the rate constants are already higher in the imidazolium ionic liquids thatn in the aprotic molecular solvents. Abstract: The tris(2, 2′-bipyridyl) complexes of cobalt(II) and (III) ([Co(bpy)3 ] 2+/3+ ) produce a redox couple of great interest in thermoelectrochemical cells and dye sensitized solar cells including both types of devices based on ionic liquid electrolytes. We present a systematic study of the electrochemistry of [Co(bpy)3 ] 2+ [NTf2 ] − 2 in two ionic liquids (ILs) based on the 1-ethyl-3-methylimidazolium (C2 mim) cation and two ILs based on the 1-butyl-1-methylpyrrolidinium cation (C4 mpyr), as well as three aprotic molecular solvents. Platinum (Pt) and glassy carbon (GC) working electrodes were compared. In all solvents better electrochemical responses were observed on GC, which yielded higher currents in the cyclic voltammograms and lower rate constants for the redox reaction. The [Co(bpy)3 ] 1+/2+ couple is also readily observed, but this redox reaction is chemically irreversible, possibly because the [Co(bpy)3 ] 1+ complex dissociates. However, the [Co(bpy)3 ] 1+/2+ reaction is chemically reversible in all of the solvents studied, except 3-methoxypropionitrile, if excess of 2, 2′-bipyridyl is added to the solution.